The Epidemiology of Human Strongyloidiasis - Cimino, Rubén Oscar (2014)
An epidemiologic approach for the understanding of the public health relevance of Strongyloides stercoralis is currently much needed, due to the renewed interest in the control of soil-transmitted helminthiasis (STH). Despite this fact, the biologic difference of S. stercoralis compared to the other STH in terms of life cycle, diagnostic approach and therapeutic options leaves this nematode under uncertainties that hamper the development of control strategies. However, evidence regarding distribution and prevalence allows for the identification of its global distribution, with lack of adequate water and sanitation supplies as the most significant risk factors. The clinical aspects of this infection in immunocompromised populations also highlight its potentially severe morbidity in groups that are at higher risk for complications during infection. The availability of more accurate diagnostic tools appears as a key element for the performance of more reliable surveys, case control studies and even monitoring for the emergence of drug resistance.